Euphytica International Journal of Plant Breeding - Visser, Richard G. F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Euphytica is an international journal on theoretical and applied aspects of plant breeding. It publishes critical reviews and papers on the results of original research related to plant breeding. The integration of modern and traditional plant breeding is a growing field of research using transgenic crop plants and/or marker assisted breeding in combination with traditional breeding tools. The content should cover the interests of researchers directly or indirectly involved in plant breeding, at universities, breeding institutes, seed industries, plant biotech companies and industries using plant raw materials, and promote stability, adaptability and sustainability in agriculture and agro-industries.
Keywords: Biotechnology; Plant science; Botany; Plant pathology; Plant Sciences; Plant Genetics and Genomics; Plant Pathology; Plant Physiology; Biotechnology